Abdominal Septic Shock – Endotoxin Adsorption Treatment (ASSET) – endotoxin removal in abdominal and urogenital septic shock with the Alteco® LPS Adsorber: study protocol for a double-blinded, randomized placebo-controlled trial. Issue 1 (December 2016) - Lipcsey, Miklos; Tenhunen, Jyrki; Sjölin, Jan; Frithiof, Robert; Bendel, Stepani; Flaatten, Hans; Kawati, Rafael; Kuitunen, Anne; Tønnessen, Tor; Rubertsson, Sten
Abstract Background Severe sepsis and septic shock are common in intensive care and carry high mortality rates. In patients with Gram-negative infections, early and extensive removal of endotoxin may limit the inflammatory response that characterizes septic shock. The Alteco® LPS Adsorber (hereafter referred to cited as the lipopolysaccharide (LPS) Adsorber) can be used for endotoxin removal and attenuate the deleterious inflammatory and clinical responses seen in septic shock. Methods/design The Abdominal Septic Shock – Endotoxin Adsorption Treatment (ASSET) trial is a pilot study investigating the feasibility and safety of LPS Adsorber therapy. This pilot, multicenter, stratified, parallel, double-blinded, randomized, phase IIa, feasibility clinical investigation will be performed in five Scandinavian intensive care units. Thirty-two subjects with early septic shock and organ failure, following adequate resuscitation, will be randomized to receive either: extracorporeal veno-venous hemoperfusion therapy with the LPS Adsorber or veno-venous hemoperfusion therapy with a placebo adsorber (without active LPS-binding peptide). Patients will be stratified by infection focus such that 20 subjects with an abdominal focus (stratum A) and 12 subjects with a urogenital focus (stratum B) will be included in a parallel design. Thereafter, an interim analysis will be performed and an additional 12 patients may be included in the study. The study is designed as adaptive a priori: the patients from this study can be included in a later phase IIb study. The aim of the study is to investigate the feasibility of LPS Adsorber therapy commenced early in the time-course of septic shock. The primary endpoint will be a characterization of all reported unanticipated serious adverse device effects and anticipated serious adverse device effects. Secondary outcomes are decrease in endotoxin plasma concentration, impact on clinical outcome measures and impact on inflammatory response by LPS Adsorber therapy, as well as detailed description of the relevant mediators bound to the LPS Adsorber. Recruitment of patients will start in September 2015. Discussion The ASSET trial will give insight into the feasibility and safety of this LPS Adsorber therapy and preliminary data on its potential clinical effects in septic shock. Moreover, this pilot trial will provide with necessary data for designing future studies. Trial registration ClinicalTrials.gov IdentifierNCT02335723 . Registered on 28 November 2014.